Patent portfolio diversity, technology strategy, and firm value - Lin, Bou-Wen; Chen, Chung-Jen; Wu, Hsueh-Liang (IEEE transactions on engineering management, 2006)
This paper investigates how the composition and diversity of a firm's patent portfolio can create synergy and, thus, contribute to firm performance. To resolve two conflicting views on whether technology diversity or strategic focus can improve firm performance, we develop a scheme to measure the diversity of a patent portfolio at the two levels of broad technology diversity and core field diversity. In our framework, both views can be valid. The former argument is effective when the focal firm has very high technology stocks and profitability is used as a performance measure. The latter is true for a focal firm with above average technology stocks and where shareholder value is considered as a performance indicator. This paper highlights technology stocks as a moderator between the relationship of technology diversity and firm performance. Generally, a firm without very high-technology stocks should concentrate its R&D resources on a specific technology field, and even within the core technology field the firm should stay focus on a small number of core technologies. Results support the competence-based view of the firm. Technology-based firms should develop a portfolio with a clear technology focus. This study lays the groundwork for future study on the interrelationships of technology strategy, patent portfolio, and long-term performance.